Noch ein Namensspiel in der Bibel?: Zum Namen Tirhaḳah in 2Kön 19,9 und Jes 37,9 - Theis, Christoffer (Biblische Notizen, 2014)
The rendering of the Egyptian monarch’s name v#h#rq# through the Hebrew hq'h'r>ti in 2Kings 19,9 and Isaiah 37,9 is compared linguistically with other ancient sources. It is argued that, through a metathesis of two consonants in the Hebrew, a subliminal meaning of hq'h'r>ti, “You shall leave (the country),” is produced, and this is connected with two historical events during the king’s reign.
Keywords: Bibel -- Könige -- 2. -- 19,9; Bibel -- Jesaja -- 37,9; Königsname; Bibel / Jesaja; Bibel / Könige